Strategi Pelayanan Perpustakaan di Era Pandemi Covid-19 pada Dinas Perpustakaan dan Kearsipan Provinsi NTB - Arini Purnamasari; Muhammad Ali; Iwin Ardyawin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study aims to determine the strategy of library services in the era of the covid-19 pandemic and to determine the supporting factors and inhibiting factors of library services in the era of the covid-19 pandemic at the Library and Archives Service of West Nusa Tenggara Province. The research method used in this research is descriptive qualitative research method. Sources of data in this study are primary data sources and secondary data. The technique of determining the informants used purposive sampling. Data collection techniques used in this study were observation, interviews, and documentation. The data analysis used in this research is an interactive analysis model. The results of research conducted at the Office of the Library and Archives of West Nusa Tenggara Province can be seen that in general the Office of the Library and Archives of West Nusa Tenggara Province has implemented a library service strategy. The library service strategy in the Covid-19 pandemic era at the West Nusa Tenggara Provincial Library and Archives Service is based on the West Nusa Tenggara Provincial Regulation Number 10 of 2019 concerning Regional Innovation which includes: the NTBelib application, iDepositNTB and Mobile Literacy Cafe Car (Feeling). Based on the results of the study, it can also be seen that the strategy carried out by the Office of the Library and Archives of West Nusa Tenggara Province has not provided optimal library services to the user community because it is influenced by inhibiting factors.